2023
DOI: 10.7759/cureus.38632
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Hand-Grip: Unraveling the Association

Abstract: This review article explores the association between hand-grip strength and depression. A total of 14 studies were carefully considered to provide a comprehensive analysis of the topic. The studies reveal a consistent association between low hand-grip strength and depressive symptoms, independent of age, gender, and chronic disease status. The evidence suggests that hand-grip strength assessment could be a useful tool for identifying individuals at risk of depression, particularly older adults and those with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Patients with depression could serve as an interesting control group, given that studies have demonstrated a lower HGS in this population compared to healthy controls. This reduced HGS was linked to the severity of depression and an increased risk of cognitive decline [33]. Furthermore, it is essential to note that this study exclusively involved women patients, as the majority of patients with ME/CFS re women.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with depression could serve as an interesting control group, given that studies have demonstrated a lower HGS in this population compared to healthy controls. This reduced HGS was linked to the severity of depression and an increased risk of cognitive decline [33]. Furthermore, it is essential to note that this study exclusively involved women patients, as the majority of patients with ME/CFS re women.…”
Section: Discussionmentioning
confidence: 99%